Cognitive reserve: implications for diagnosis and prevention of Alzheimer's disease. - Scarmeas, Nikolaos; Stern, Yaakov (Curr Neurol Neurosci Rep, 2004)
Epidemiologic evidence suggests that higher occupational attainment and education, as well as increased participation in intellectual, social, and physical aspects of daily life, are associated with slower cognitive decline in healthy elderly and may reduce the risk of incident Alzheimer's disease (AD). There is also evidence from structural and functional imaging studies that patients with such life experiences can tolerate more AD pathology before showing signs of clinical dementia. It has been hypothesized that such aspects of life experience may result in functionally more efficient cognitive networks and, therefore, provide a cognitive reserve that delays the onset of clinical manifestations of dementia. In this article, we review some of the relevant literature of the noted associations between markers of cognitive reserve and AD and discuss the possible mechanisms that may explain these associations.
Keywords: Activities of Daily Living; Alzheimer Disease; Cognition; Educational Status; Environment; Humans; Life Style; Occupations